Prescribers prefer people: The sources of information used by doctors for prescribing suggest that the medium is more important than the message - McGettigan, P (Blackwell Science Inc, 2001)
AIMS: The sources of prescribing information are legion but there is little knowledge about which are actually used in practice by doctors when prescribing. The aims of this study were to determine the sources of prescribing information considered important by doctors, establish which were used in practice, and investigate if hospital and primary care physicians differed in their use of the sources. METHODS: Two hundred general practitioners (GPs) and 230 hospital doctors were asked to rate information sources in terms of their importance for prescribing ‘old’ and ‘new’ drugs, and then to name the source from which information about the last new drug prescribed was actually derived. RESULTS: Among 108 GPs, the Drugs and Therapeutics Bulletin and medical journal articles were most frequently rated as important for information on both old and new drugs while pharmaceutical representatives and hospital/consultant recommendations were more important for information on new drugs, as opposed to old. In practice, information on the last new drug prescribed was derived from pharmaceutical representatives in 42% of cases and hospital/consultant recommendations in 36%, with other sources used infrequently. Among 118 hospital doctors, the British National Formulary (BNF) and senior colleagues were of greatest theoretical importance. In practice, information on the last new drug prescribed was derived from a broad range of sources: colleagues, 29%; pharmaceutical representatives, 18%; hospital clinical meetings, 15%; journal articles, 13%; lectures, 10%. GPs and hospital doctors differed significantly in their use of pharmaceutical representatives (42% vs 18%) and colleagues (7% vs 29%) as sources of prescribing information (P < 0.0001 for both). CONCLUSIONS: The sources most frequently rated important in theory were not those most used in practice, especially among GPs. Both groups under-estimated the importance of pharmaceutical representatives. Most importantly, the sources of greatest practical importance were those involving the transfer of information through the medium of personal contact.